A randomized, controlled, phase II clinical trial of β‐D‐mannuronic acid (M2000) in pre‐surgical breast cancer patients at early stage (T1‐T2). (26th April 2019) - Kashefi, Sarvenaz; Omranipour, Ramesh; Mahmoodzadeh, Habibollah; Ahmadi, Hamid; Alikhassi, Afsaneh; Hosseini, Mostafa; Cuzzocrea, Salvatore; Rehm, Bernd H. A.; Matsuo, Hidenori; Mirshafiey, Abbas
Summary: Following the potent efficacy of β‐D‐Mannuronic acid in a breast cancer murine model, we evaluated the efficacy of this novel non‐steroidal anti‐inflammatory drug in breast cancer patients in the present clinical trial. The study was an 8‐week randomized, controlled, phase II clinical trial (IRCT: 2017012213739N7 (in 48 pre‐surgical breast cancer patients. Patients who had breast cancer at early stage, with invasive ductal carcinoma, were placed on a waiting‐list for surgery and were allocated to the study. β‐D‐Mannuronic was administrated at a dose of two capsules (1000 mg/d) orally during a period of 8 weeks. The end point of this study was when the patients were admitted for surgery. Moreover, the patients' well‐being status was followed up on for safety. There were no statistically significant differences between treatment and non‐treatment groups at baseline. β‐D‐Mannuronic acid therapy, from 20 patients, showed that in one patient (5%) tumour size was decreased; in five patients (25%) tumour growth was stopped; and in 14 patients (70%) the growth rate in the treatment group did not show significant change, compared to the non‐treatment group. Evaluation of two tumour markers (carcinoembryonic antigen and cancer antigen 15‐3) showed that there was no significant difference between before and after treatment. Although the use of some non‐steroidal anti‐inflammatory drugs in a long time period has shown a prophylactic effect in breast cancer, their therapeutic efficacy in a short time period is unknown, whereas treatment with β‐D‐Mannuronic acid during 8 weeks could show 30% therapeutic effects in pre‐surgical breast cancer patients.